2021
DOI: 10.1353/hpu.2021.0066
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based Health Education Resources for Indigenous Adults: A Scoping Review

Abstract: Indigenous peoples experience a disparate burden of chronic diseases and lower access to health education resources compared with other populations. Technology can increase access to health education resources, potentially reducing health inequities in these vulnerable populations. Although many Indigenous communities have limited access to the Internet, this barrier is decreasing as tribes and Indigenous-serving organizations work to improve TechQuity. Using Arksey and O'Malley's framework, we conducted a sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…Prior research has found that online education programs can be effectively administered in the general population (Holt et al, 2019). More specifically, data show that online and technology-based interventions may lead to positive health outcomes in Indigenous communities (Stotz et al, 2021). For example, an intervention that included website interaction led to increased amounts of self-reported physical activity (Albright et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that online education programs can be effectively administered in the general population (Holt et al, 2019). More specifically, data show that online and technology-based interventions may lead to positive health outcomes in Indigenous communities (Stotz et al, 2021). For example, an intervention that included website interaction led to increased amounts of self-reported physical activity (Albright et al, 2014).…”
Section: Introductionmentioning
confidence: 99%